ACCOUNTING INFORMATION SYSTEM FOR SALES AND CASH RECEIPTS (CASE STUDY AT BANGUNG CINTA ALAM) - Aniek Murniati (Management Study Program, Faculty of Economics, Merdeka University Pasuruan. East Java. Indonesia, 2025)
The purpose of this study is to determine the sales receipt accounting system in PT. Bangun Cinta Alam sales. Does the accounting information system at PT. Bangun Cinta Alam already has an internal control system in place; is it effective and efficient? In this study, data collection was conducted using field research techniques, including interviews with leaders and employees, observation, and documentation. While library research was obtained from literature and books related to the research conducted, the author used qualitative descriptive data analysis techniques. This research was conducted at PT. Bangun Cinta Alam. Based on the results of the research and discussion conducted, it is concluded that the sales accounting information system of PT. Bangun Cinta Alam has fulfilled the elements of internal control. The company's cash receipt or sales accounting system is appropriate and effective because it aligns with the elements of internal control, thereby supporting the cash receipt system effectively.